Aetiology, antimicrobial susceptibility patterns and factors associated with bacteriuria among HIV-infected women attending Prevention of Mother-to-Child Transmission (PMTCT) clinic at Bukoba Municipality, Tanzania - Eustadius Kamugisha Felician; Loveness Urio; Mtebe Majigo; Said Aboud (PLoS ONE, 2025)
Background Bacteriuria is the detection of significant bacteria in urine in the presence or absence of signs and symptoms of urinary tract infection (UTI). Bacteriuria in pregnant and lactating HIV-infected women can cause serious complications to women and fetuses for pregnant women. Due to the importance of bacteriuria, we determined the etiology, antimicrobial susceptibility patterns, and factors associated with bacteriuria in HIV-infected women. Methods We conducted a cross-sectional study from January to April 2022 among HIV-infected women attending the Prevention of Mother-to-Child Transmission (PMTCT) clinic at Bukoba Municipality, Tanzania. Clean-catch midstream urine specimens were collected for culture on MacConkey and blood agars. We used colonial characteristics, Gram staining reactions, and biochemical tests to identify bacteria isolates. Data were collected using a structured questionnaire. We used STATA version 15.0 for analysis. An association with bacteriuria was performed using modified poisson regressions. A p-value ≤ 0.05 was regarded as statistically significant. Results Of the 290 participants, 66 (22.8%) had significant bacteriuria. The predominant bacteria isolates were Escherichia coli 21 (31.8%). Among gram-negative bacteria, 17 (34.0%) were extended-spectrum beta-lactamase producers, and 1 (25.0%) of Staphylococcus aureus were Methicillin-resistant. Escherichia coli showed a high rate of resistance against trimethoprim-sulfamethoxazole 21 (100%), and amoxicillin clavulanic acid 20 (95.0%). Staphylococcus aureus was highly resistant to penicillin 4 (100%) and trimethoprim-sulfamethoxazole 4 (100%). The proportion of multi-drug resistant (MDR) strains was 45 (68.2%). Conclusions The prevalence of bacteriuria in HIV-infected women was relatively high. The pathogens were most resistant to trimethoprim-sulfamethoxazole, penicillin and amoxicillin clavulanic acid and more than two-third were MDR. The findings emphasize that the use of antimicrobial agents should be supported by culture and Antimicrobial Susceptibility Testing (AST) results.